The Plural Subject Approach to Social Ontology and the Sharing Values Issue - Francesca De Vecchi (Rosenberg & Sellier, 2016)
I address the issue of the unity of social ontology despite the extreme variety of social entities: groups, money, promises, governments, laws, etc. Then, I focus on Gilbert’s account of social ontology as an ontology specifically dealing with groups as plural subjects, and face with Gilbert’s concept of shared values as values of plural subjects created by joint commitment. I argue that Gilbert’s account of shared values is a cognitivist and extrinsic one: it neglects the specific role of values for the constitution of plural subjects and considers values neither as a necessary nor as a sufficient condition for social unity. I suggest that, unlike Gilbert and the main trend in the contemporary social ontological debate, phenomenology provides an axiology that can allow to account adequately for values and to understand values’ crucial role for social unity. I discuss Scheler’s dividing vs. sharing values thesis and mention Schapp’s collective values thesis. Finally I address the question of the collective feeling value.